2012
DOI: 10.1152/jn.00355.2012
|View full text |Cite
|
Sign up to set email alerts
|

Motor learning reveals the existence of multiple codes for movement planning

Abstract: Hudson TE, Landy MS. Motor learning reveals the existence of multiple codes for movement planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
1

Year Published

2014
2014
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 40 publications
6
32
0
1
Order By: Relevance
“…We have previously shown that motor planning during unperturbed reaches is based on both a polar and a Cartesian coordinate encoding, even for the identical reaches (Hudson & Landy, 2012a), and it is clear that these plans can be updated when an imposed perturbation is apparent [when it is large and/or self-imposed, such as when using a tablet-based input device, e.g., Wu & Smith (2013), who used large perturbations of drawing/tracing movements]. Here, we examined whether motor plans in both coordinate systems are updated in response to perturbations that are too small to be noticed, consistent with the notion of an automatic sensory-motor adaptive response as opposed to a deliberate, cognitively mediated correction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that motor planning during unperturbed reaches is based on both a polar and a Cartesian coordinate encoding, even for the identical reaches (Hudson & Landy, 2012a), and it is clear that these plans can be updated when an imposed perturbation is apparent [when it is large and/or self-imposed, such as when using a tablet-based input device, e.g., Wu & Smith (2013), who used large perturbations of drawing/tracing movements]. Here, we examined whether motor plans in both coordinate systems are updated in response to perturbations that are too small to be noticed, consistent with the notion of an automatic sensory-motor adaptive response as opposed to a deliberate, cognitively mediated correction.…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was run using the Psychophysics Toolbox software (Brainard, 1997; Pelli, 1997) and the Northern Digital API (for controlling the Optotrak). Details of the apparatus and method of calibration are the same as used previously (Hudson & Landy, 2012a,b). …”
Section: Methodsmentioning
confidence: 99%
“…We demonstrated the use of the method for identifying regions of movement impairment, in individuals with upper limb hemiparesis due to a stroke, and how it can be applied as a basis for performance-based selection of training movements for rehabilitation. The advantages of the performance mapping principle are that (1) mapping spans a wide region of the reaching movement conditions, and is fine-grained, potentially allowing high sensitivity to patterns of motor impairment, which may be overlooked by coarser clinical diagnostic scores (2) it is reasonably quick and easy to produce and to interpret, and (3) the maps’ coordinates (movement and target directions) relate to established basic elements of movement coding [2227]. The mapping principle can be easily applied to any quantifiable scalar measures of reaching performance – behavioural metrics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The range of target and start locations tests both postural and movement-related aspects of motor control, respectively. Importantly, muscle activation patterns and population neural activity in the motor-related cortices show tuning to one or both task dimensions [2225], and behavioural studies support the essential underlying role of these parameters in planning of reaching movements [26, 27]. …”
Section: Introductionmentioning
confidence: 99%
“…В тоже время, подобие распределений по выбранному критерию (хи-квадрат) свидетельствует в пользу того, что при запоминании используется позиционное кодирование положений фигуры на шахматной доске. Подобные распределения ошибок человека в моторных задачах также были интерпретированы как проявление искажений при воспроизведении позиционно закодированных стимулов в [17]. Отметим, что при использовании иного стимульного материала или иной инструкции для испытуемых в рабочей пространственной памяти может осуществляться и векторное кодирование, для которого характерны принципиально иные распределения ошибок [10,11,17].…”
Section: Discussionunclassified